Remote patient monitoring in autoimmune related interstitial lung diseases: a narrative review - Althobiani, Malik A.; Almoagal, Maryam (Frontiers in Immunology, 2025)
Autoimmune related interstitial lung disease can worsen between clinic visits, and episodic assessment may miss clinically important change. Digital health extends observation into daily life through home spirometry, wearable sensors, application based patient reported outcomes, and therapist supported telerehabilitation. This Review synthesizes recent evidence on feasibility and adherence, data quality and agreement with clinic assessments, patient experience and safety, and service integration for remote monitoring in autoimmune related interstitial lung disease. Device derived signals and patient generated health data show useful agreement with clinic measures when interpreted across repeated time points, and remote monitoring data can reveal actionable trends and support rehabilitation and self-management. Important limitations remain, including variability and artifacts, missing data, uneven interoperability, workload implications for services, and inequities in digital access. We outline a practical workflow for adoption that includes enrolment, training, quality checks, alert thresholds, and escalation to the multidisciplinary team, with attention to privacy, cost, and record integration. Remote monitoring can complement standard care by increasing observation frequency and patient support. Priorities for the field are to define clinically meaningful digital endpoints, evaluate effects on outcomes and use of resources, and develop strategies that sustain long term engagement.